Portal hypertension in common variable immunodeficiency disorders – a single center analysis on clinical and immunological parameter in 196 patients - Hanitsch, Leif G.; Steiner, Sophie; Schumann, Michael; Wittke, Kirsten; Kedor, Claudia; Scheibenbogen, Carmen; Fischer, Andreas (Frontiers in Immunology, 2023)
Background Liver manifestations and in particular portal hypertension (PH) contribute significantly to morbidity and mortality of patients with common variable immunodeficiency disorders (CVID). Screening strategies and early detection are limited due to the lack of specific diagnostic tools. Methods We evaluated clinical, immunological, histological, and imaging parameters in CVID patients with clinical manifestation of portal hypertension (CVID+PH). Results Portal hypertension was present in 5.6% of CVID patients and was associated with high clinical burden and increased mortality (18%). Longitudinal data on clinical and immunological parameters in patients before and during clinically manifest portal hypertension revealed a growing splenomegaly and increasing gamma-glutamyl transferase (GGT) and soluble interleukin 2 receptor (SIL-2R) levels with decreasing platelets over time. While ultrasound of the liver failed to detect signs of portal hypertension in most affected patients, transient elastography was elevated in all patients. All CVID+PH patients had reduced naïve CD45RA+CD4+ T-cells (mean of 6,2%). The frequency of severe B-lymphocytopenia (Euroclass B-) was higher in CVID+PH patients. The main histological findings included lymphocytic infiltration, nodular regenerative hyperplasia-like changes (NRH-LC), and porto(-septal) fibrosis. Conclusion CVID patients with lower naïve CD45RA+CD4+ T-cells or severely reduced B-cells might be at higher risk for portal hypertension. The combination of biochemical (increasing sIL-2R, GGT, and decreasing platelets) and imaging parameters (increasing splenomegaly) should raise suspicion of the beginning of portal hypertension.